2019
DOI: 10.1101/740191
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-term effects of GPS collars on the activity, behavior, and adrenal response of scimitar-horned oryx (Oryx dammah)

Abstract: 28GPS collars have revolutionized the field of animal ecology, providing detailed information on 29 animal movement and the habitats necessary for species survival. GPS collars also have the 30 potential to cause adverse effects ranging from mild irritation to severe tissue damage, reduced 31 fitness, and death. The impact of GPS collars on the behavior, stress, or activity, however, have 32 rarely been tested on study species prior to release. The objective of our study was to provide a 33 comprehensive as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Alternatively, quantifying behavioural responses post‐capture can provide useful species‐specific information on altered behaviour and inform future studies (Dechen Quinn et al, 2012; Picardi et al, 2022). For example, Stabach et al (2020) examined effects of GPS collar deployment on scimitar‐horned oryx Oryx dammah to quantify the short‐term responses in activity, behaviour, stress levels and the length of time before these effects subsided.…”
Section: Example Applicationsmentioning
confidence: 99%
“…Alternatively, quantifying behavioural responses post‐capture can provide useful species‐specific information on altered behaviour and inform future studies (Dechen Quinn et al, 2012; Picardi et al, 2022). For example, Stabach et al (2020) examined effects of GPS collar deployment on scimitar‐horned oryx Oryx dammah to quantify the short‐term responses in activity, behaviour, stress levels and the length of time before these effects subsided.…”
Section: Example Applicationsmentioning
confidence: 99%
“…Alternatively, quantifying behavioral responses post-capture can provide species-specific information on altered behavior and inform future studies (Dechen Quinn et al, 2012). For example, Stabach et al (2020) examined effects of GPS collar deployment on scimitar-horned oryx ( Oryx dammah ) to quantify the short-term responses in activity, behavior, and stress levels, and the length of time before these effects subsided. Visual observation showed headshaking significantly increased post-capture but returned to pre-capture levels within 3 days, and random forest classification of tri-axial accelerometer data indicated a 480% increase in headshaking compared to stable baseline levels that resumed after 24 hours.…”
Section: Example Applicationsmentioning
confidence: 99%
“…Visual observation showed headshaking significantly increased post-capture but returned to pre-capture levels within 3 days, and random forest classification of tri-axial accelerometer data indicated a 480% increase in headshaking compared to stable baseline levels that resumed after 24 hours. Using piecewise regression, Stabach et al (2020) found that fecal glucocorticoid metabolite levels were elevated for five days following collar deployment, suggesting a stress response, before returning to baseline levels.…”
Section: Example Applicationsmentioning
confidence: 99%
“…(8) (9)), drag is negligible in terrestrial (though not aerial) systems even though tag detriment in terrestrial animals has been widely reported and is multi-facetted (10). For example, cited issues range from minor behavioral changes (11) through skin-, subcutaneous-and muscle damage with ulceration (12,13) to reduced movement speed (14) and dramatically increased mortality (15). As with drag, we advocate that a force-based framework is necessary to help understand such detriment.…”
mentioning
confidence: 99%